2017
DOI: 10.1016/j.canlet.2017.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Melittin, a major peptide component of bee venom, and its conjugates in cancer therapy

Abstract: Melittin (MEL), a major peptide component of bee venom, is an attractive candidate for cancer therapy. This agent has shown a variety of anti-cancer effects in preclinical cell culture and animal model systems. Despite a convincing efficacy data against variety of cancers, its applicability to humans has met with challenges due to several issues including its non-specific cytotoxicity, degradation and hemolytic activity. Several optimization approaches including utilization of nanoparticle based delivery of ME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
260
0
12

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 300 publications
(275 citation statements)
references
References 103 publications
3
260
0
12
Order By: Relevance
“…The successful use of the membrane‐active lipopeptide antibiotics daptomycin and telavancin in clinical medicine indicate that selectivity toward bacterial membranes is possible . Infact, a highly hemolytic peptide such as melittin is used for killing cancer cells by use of hydrogels . Unlike model peptides that may exhibit immune response on fatty acylation, host‐defense peptides such as cationic segments of defensins are not likely to elicit immune responses and could be attractive candidates for development as therapeutic agents.…”
Section: Discussionmentioning
confidence: 99%
“…The successful use of the membrane‐active lipopeptide antibiotics daptomycin and telavancin in clinical medicine indicate that selectivity toward bacterial membranes is possible . Infact, a highly hemolytic peptide such as melittin is used for killing cancer cells by use of hydrogels . Unlike model peptides that may exhibit immune response on fatty acylation, host‐defense peptides such as cationic segments of defensins are not likely to elicit immune responses and could be attractive candidates for development as therapeutic agents.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, honeybee venom contains many low molecular mass compounds such as sugars, amino acids, phospholipids, pheromones and biogenic amines [2]. Extensive research conducted in recent years has shown that satisfactory results may be achieved when using bee venom for various types of diseases such as arthritis [3], chronic pain [4], cancer [5] and atopic dermatitis [6]. The major component of bee venom is called melittin.…”
Section: Introductionmentioning
confidence: 99%
“…Although, it is composed of a diverse range of proteins and peptides, melittin is the major protein and comprises about 50% (w/w) of dry bee venom (Gajski and Garaj-Vrhovac, 2013). Melittin has anti-analgesic, anti-inflammatory, and antimicrobial activities (Gajski and Garaj-Vrhovac, 2013;Lin et al, 2017;Rady et al, 2017;Shi et al, 2016). However, no reports of melittin on lung cancer proliferation and monocyte differentiation are available.…”
mentioning
confidence: 99%